Diseño Universal del Aprendizaje en la Unidad Educativa Cristiana “Nazareno”. Riobamba. - Villacís Albán, Melany Jeaneth (2025)
The Universal Design for Learning (UDL) is an educational approach that seeks to provide all students with equal opportunities to learn, eliminating barriers that may exist in the educational process. This research focuses on evaluating the implementation of the UDL in "Unidad Educativa Cristiana Nazareno," with a particular focus on teachers and their role in applying this model. The main objective of this study is to analyze how teachers at the "Unidad Educativa Cristiana Nazareno" implement the UDL principles in their pedagogical practices and how they impact creating an inclusive educational community. For this purpose, a survey was used to collect the main criteria and experiences regarding this new pedagogical approach. The results show that teachers significantly understand and apply UDL principles in their pedagogical practices, which denotes an effort to address diversity in the classroom. However, gaps and opportunities for improvement are evident, such as constant training and diversity of resources. In conclusion, this research seeks to contribute to the knowledge about Universal Design for Learning and its application in specific educational contexts, highlighting the importance of teachers' role in creating inclusive and accessible learning environments for all students.